S68 Copd in the ed: eosinophils, treatment and outcomes, data from the pre-award study. (15th November 2016) - Russell, REK; Doggett, T; Pavord, I; Pullinger, R; Beer, S; Bafadhel, M
Abstract : Rationale: Acute exacerbations of COPD (AECOPD) are common. Peripheral blood eosinophil count (PBE) predicts outcomes in moderate and severe exacerbations, but little is known about PBE levels and outcomes of AECOPD in the emergency department (ED). Methods: Data for all attendances to ED of a large teaching hospital throughout a 12-month period for patients attending with AECOPD were studied. Anonymised data was cleaned to remove diagnostic and data errors and analysed using GraphPadPrism6 with statistical methods suitable for the data collected. Data is presented as mean (SEM). Data collected included: demography, length of stay (LOS), vital status, initial treatment, full blood counts, renal function and CRP. Results: There were 549 patients, with 768 AECOPD events. The mean (SD) age was 71 years and 192 episodes were associated with an eosinophil count >2% (26.6%). There were 403 (56%) AECOPD episodes leading to admission; there was no difference in the eosinophil count between patients admitted or discharged from ED. Absolute and relative PBE levels were increased in patients re-attending ED (Absolute PBE mean difference 0.08, 95% CI: 0.02 to 0.13, p = 0.007; %PBE mean difference 0.6, 95% CI: 0.14 to 1.1, p = 0.001). Patients with a PBE > 2% were readmitted more often (p = 0.002, RR 1.16, 95% CI: 1.05 to 1.26). For patients admitted, mean LOS was reduced if admission %PBE levels were >2% (4.6 (0.5) vs. 5.8 (0.3) days, p = 0.012). In patients known to have received oral corticosteroids in ED, the reduction in LOS was greater still if the %PBE was >2% compared to ≤2% (mean (SD) 4.1 (1.0) vs. 6.5 (0.9), p = 0.046). In-patient mortality occurred in 35 patients and occurred more frequently in patients with a %PBE ≤ 2% (RR 1.16, 95% CI: 1.04 to 1.68, p = 0.012). Conclusions: This real-world data suggests that PBE levels may be a useful marker for predicting important clinical outcomes in AECOPD.